ETIKA BISNIS DALAM PERSPEKTIF EKONOMI SYARI'AH: TELAAH ATAS KASUS BERAS OPLOSAN DI INDONESIA DALAM SUDUT PANDANG EKONOMI SYARI’AH - Solekhan, Ahmad (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2025)
The case of rice adulteration—mixing low-quality rice and selling it as premium—is a form of fraud (tadlis) that is clearly prohibited in Islamic economics. This practice violates the principles of amanah (trustworthiness) and shidq (honesty), which must be upheld in transactions. Sharia views any form of manipulation of the quality, quantity, or information of goods as a detrimental act that can invalidate the contract due to the lack of mutual consent (ridha) of both parties.From the perspective of Islamic jurisprudence (fiqh al-muamalat), rice adulteration constitutes gharar (unclearness) and ghabn fahisy (transactional injustice due to concealed quality differences). Perpetrators not only undermine market integrity but also deprive consumers of their right to obtain goods that meet the promised quality standards. In a market context, such actions are considered to undermine fair pricing mechanisms, trigger instability in food distribution, and can lead to social unrest.Overall, Islamic economics considers the practice of adulterated rice to be haram (forbidden) because it violates the principles of justice (al-'adl), transparency, and the public good (maslahah). In an Islamic economic system, producers and traders are required to maintain morality in their business activities to ensure fair and stable markets. Therefore, law enforcement and business ethics education are essential to prevent fraudulent behavior from disrupting the economic order of society.